Embracing Local Wisdom: Enriching Environmental Law Development through the Humanist Lens of Pancasila - Widyastuti, Tiyas Vika; Sanusi, Sanusi; Aryani, Fajar Dian; Idayanti, Soesi (Indonesian Journal Publisher, 2025)
The response to changes in legal frameworks is of paramount importance, particularly in the context of Indonesia's vision for an ideal legal system grounded in Pancasila. This article asserts that legal development should be attentive to existing legal sources, with a strong emphasis on norms that have been deeply integrated into cultural contexts and local wisdom. Central to Pancasila is a humanist philosophy, primarily encapsulated in its second precept, which underpins the values embraced by Indonesian society. The principles inherent in Pancasila humanism advocate for a shared national understanding, respect for democratic freedoms, social equity, and recognition of diverse religious beliefs, all while upholding human dignity and rights. This article constructs arguments for the integration of local wisdom into the legal framework governing environmental management and protection, highlighting its crucial role in ecological preservation and the well-being of the human environment. Indigenous knowledge, characterized by principles such as non-discrimination, deliberation, honesty, and harmony, emerges as a vital source of social capital that can significantly enhance the development of environmental law from the perspective of Pancasila humanism.